The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/su12103963
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Accessibility between Civil Airports and Tourist Locations in Tourist Cities in Yunnan Province, China

Abstract: Coordinated development between landside transport at civil airports and aviation networks is key for determining the attractiveness and competition of tourist cities. However, only a few studies have focused on the accessibility of tourist locations around civil airports in tourist cities in China. This paper calculates the service coverage of civil airports for tourist locations in Yunnan in selected years, consisting of 2000, 2005, 2010, and 2015, by using an accessibility calculation method with the shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Based on the consideration for ground traffic, ArcGIS10.2 is used in this paper to convert the original vector data map into raster data, so as to avoid the insufficient coverage of the accessibility measurement of non-network nodes [49]. Additionally, the traffic accessibility of Yading Airport is measured based on the highway data at all levels in Ganzi Prefecture.…”
Section: Basic Conditions Of Access: An Analysis Of Traffic Accessibi...mentioning
confidence: 99%
“…Based on the consideration for ground traffic, ArcGIS10.2 is used in this paper to convert the original vector data map into raster data, so as to avoid the insufficient coverage of the accessibility measurement of non-network nodes [49]. Additionally, the traffic accessibility of Yading Airport is measured based on the highway data at all levels in Ganzi Prefecture.…”
Section: Basic Conditions Of Access: An Analysis Of Traffic Accessibi...mentioning
confidence: 99%
“…Meanwhile, potential accessibility and realized accessibility have been defined as emphasizing the different stages of accessibility ( 9 , 10 ). In addition to the various concepts related to accessibility, studies on airport accessibility have frequently used landside accessibility as a term referring to measuring airport accessibility from the starting point by road or rail network and airside accessibility as a term referring to an airports’ connectivity and flight networks/number of passengers ( 1113 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other important issues addressed in the literature are: “access” to the systems or accessibility using different modes of transportation—by car ( 8 , 11 , 2225 ), by transit and car ( 12 , 16 , 17 , 2628 ), by public transit ( 18 ), by cycling/walking ( 19 )—and changes in accessibility over time ( 10 , 11 , 17 , 18 , 25 , 29 , 30 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, to decrease these economic, social and environmental impacts, policy maker and airport operators should carefully layout the ground transport plan (GTP) in order to cope with air passenger market segmentation, and passenger growth by balancing with airport constraints. Moreover, a study of Hao, Zhang, Ji, Wu, and Liu (2020) demonstrated interesting findings and suggestion that accessibility from airport to tourist destinations of the city should be prioritized as significant as development of airport itself. As time costs was very crucial for satisfaction and decision making of visitors for a choice of tourist destination as well as the willingness to revisit.…”
Section: Airport-city Connectivitymentioning
confidence: 99%